2022
DOI: 10.1097/rlu.0000000000004110
|View full text |Cite
|
Sign up to set email alerts
|

Is Delayed Image of 18F-FDG PET/CT Necessary for Mediastinal Lymph Node Staging in Non–Small Cell Lung Cancer Patients?

Abstract: The purpose of this study was to evaluate the diagnostic accuracies of dual-time-point (DTP) 18 F-FDG PET/CT for detection of mediastinal lymph node (LN) metastasis in non-small cell lung cancer (NSCLC) patients through a systematic review and meta-analysis. Patients and Methods: The PubMed, Cochrane database, and EMBASE database, from the earliest available date of indexing through October 31, 2021, were searched for studies evaluating diagnostic performance of DTP 18 F-FDG PET/CT for detection of metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…A meta-analysis of using delayed [ 18 F]FDG PET for differentiating benign and malignant pulmonary nodules failed to demonstrate a bene t for delayed imaging [13]. Conversely, a meta-analysis of 758 patients concluded that the diagnostic accuracy of [ 18 F]FDG PET for mediastinal lymph node metastases was improved by using the retention index of [ 18 F]FDG calculated from dual time point imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of using delayed [ 18 F]FDG PET for differentiating benign and malignant pulmonary nodules failed to demonstrate a bene t for delayed imaging [13]. Conversely, a meta-analysis of 758 patients concluded that the diagnostic accuracy of [ 18 F]FDG PET for mediastinal lymph node metastases was improved by using the retention index of [ 18 F]FDG calculated from dual time point imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [30] used a double check-in time (early and late study) of PET/CT images and concluded that they have an adequate diagnostic system for the detection of metastases in mediastinal nodes in patients with non-small cell lung cancer with the same accuracy in the early and late study. They suggested that multicenter studies should be carried out with this methodology to firmly establish the usefulness of the late images.…”
Section: Use Of Quantitativementioning
confidence: 99%
“…Lee y colaboradores (31) utilizan un doble chequeo en el tiempo (estudio temprano y estudio tardío) de las imágenes PET/CT y concluyen que, de esta manera, se tiene un adecuado sistema diagnóstico en la detección de metástasis en ganglios mediastinales en pacientes con cáncer de pulmón de células no pequeñas, teniendo la misma exactitud en el estudio temprano y tardío. Sugieren que se realicen estudios multicéntricos con esta metodología, a fin de establecer firmemente la utilidad de las imágenes tardías.…”
Section: Utilización De Parámetros Cuantitativosunclassified